Capacity Enhancement among Banks’ Employees for ESRM Skill Enhancement: A Case of Nepalese Commercial Banks - Vaidya, Rashesh; Pradhan, Prajan; Ghimire , Ajaya (Khwopa Journal, 2025)
This study examines capacity enhancement initiatives for Environmental and Social Risk Management (ESRM) skill development across Nepal’s commercial banks, categorized by ownership. Through a quantitative evaluation of training programs and competency gaps, the research reveals a decisive, large-scale strategic commitment to ESRM. Financial investments are substantial and varied for the period of F/Y 2021-22 to F/Y 2024-25: Joint Venture banks lead with NPR 29.6 million allocated, followed by Nepalese Investors’ Owned (NPR 18.1 million) and Government-Owned banks (NPR 6.5 million). Training scale also differs; Nepalese Investors’ Owned banks conducted the most sessions (294) for the largest audience (7,104 attendees), whereas Joint Venture banks focused on 246 trainings for 5,269 employees, suggesting deeper engagement. Government banks conducted fewer, more concentrated sessions. This data signifies an industry-wide evolution from building specialist cadres towards embedding a resilient, bank-wide ESRM culture as a ‘first line of defense.’ The maturation is evident in the exponential growth in funding, training frequency, and employee reach. The study concludes that to sustain this progress, banks must advance towards structured competency-based frameworks, supported by regulatory reinforcement and industry collaboration. Strengthening ESRM proficiency is critical for improving risk management, ensuring compliance, and promoting sustainable financial practices in Nepal.